2011
DOI: 10.1002/ijc.25894
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical development of highly effective and safe DNA vaccines directed against HPV 16 E6 and E7

Abstract: To allow vaccination irrespective of HLA type, DNA vaccines encoding full-length antigens are required. However, here, we demonstrate that the immunogenicity of DNA vaccines encoding the full-length human papillomavirus (HPV) type 16 E7 and E6 proteins is highly reduced compared to vaccines encoding only the immunodominant epitope. Furthermore, the low remaining immunogenicity is essentially lost for both E7 and E6 when a nononcogenic ''gene-shuffled" variant is utilized. To address these issues, we tested whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…In previous mouse studies, DNA vaccination with the tumorassociated antigens AH1 and E7 induced CD8 + cell-dependent regression of established tumors that expressed those antigens (33,74). In the studies presented here, fusion of the TEM1 antigen to the TT adjuvant increased the immunogenicity of the target antigen and the efficacy of tumor control.…”
Section: Methodssupporting
confidence: 54%
“…In previous mouse studies, DNA vaccination with the tumorassociated antigens AH1 and E7 induced CD8 + cell-dependent regression of established tumors that expressed those antigens (33,74). In the studies presented here, fusion of the TEM1 antigen to the TT adjuvant increased the immunogenicity of the target antigen and the efficacy of tumor control.…”
Section: Methodssupporting
confidence: 54%
“…Cells were resuspended in FACS buffer (PBS, pH 7.2 containing 1% BSA and 0.1% sodium azide) and stained with Alexa 488-conjugated anti-CD8α mAb (BD Pharmingen) and allophycocyanin-conjugated H-2K b E6 48–57 (EVYDFAFRDL) tetramer [32](NIH Tetramer Facility, Atlanta, GA, USA) for 30 min at 4°C. Cells were washed and resuspended in FACS buffer and samples were acquired using a FACSaria (Becton Dickinson, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…23 The low immunogenicity of pVAX-E7SH is rescued in these studies with the addition of helper epitopes and a retention signal with insertion of SigHelp-KDEL. 33 In a previous study using VREP particles, the insertion of SigHelp-KDEL resulted in a higher percentage of E7-specific effector T cells at both early and late time points after immunization. 24 Significant differences in the effector memory T cell phenotype was only significantly higher early after immunization.…”
Section: Discussionmentioning
confidence: 88%
“…However, as seen by others pVAX was also not immunogenic at a dose of 10 µg or less, regardless of the administration method. 23,33 In those studies there were also no detectable responses observed with repeated administrations of 20 µg of pVAX, with anti-tumor control only demonstrated within the context of an optimized DNA vector. 23 …”
Section: Discussionmentioning
confidence: 93%